A Not So Lonely Planet : Framing Sustainable Travel on Lonely Planet’s Website: A Comparative Study - Suoranta, Sanna (My University, 2021)
This thesis examines how the world’s largest travel guide publisher Lonely Planet addresses and frames the subject of sustainable travel in the articles and news featured on its website. The study is comparative, and the Paris Agreement established in late 2015 operated as a dividing point according to which the data was divided into two corpora. A comparison of the texts published between 2010–2015 and 2016–2020 was done by utilizing frame analysis and methods from corpus linguistics. Using both quantitative and qualitative methods, the two corpora were inspected in relation to three frames—the economic, environmental, and social frame—which were established following the three pillars of sustainability and United Nations World Tourism Organization’s Sustainable Development Goals. The results indicate that Lonely Planet addresses sustainable travel on its website primarily by promoting the sustainability actions of businesses, cities, and communities as well as by advertising sustainable destinations. In general, Lonely Planet frames sustainable travel through all of the three frames, but the environmental frame is dominant in both corpora. Lonely Planet constructs the frames similarly in both corpora, but the 2016–2020 texts evidently feature more Sustainable Development Goals and overall address the subject of sustainable travel more. According to the results, Lonely Planet discusses the subject of sustainable travel in both corpora and the subject is becoming more topical as the company addresses it substantially more in its 2016–2020 texts. It concludes that higher-level actors ought to utilize their authoritative voice in promoting and implementing sustainable travel. By setting an example, these higher-level actors can inspire individuals to travel sustainably, which can further reduce the negative economic, environmental, and social impacts of traveling.